Longitudinal Study on the Lifestyle and Health of University Students (ELESEU): design, methodological procedures, and preliminary results - Patrícia Simone Nogueira (Cadernos de Saúde Pública, 2018)
Admission to a university may cause significant changes in the pattern of exposure to health risks. The aim of this paper is to describe the study design and methodological procedures adopted in the Longitudinal Study on the Lifestyle and Health of University Students (ELESEU). This study examines a dynamic cohort of full-time students at a public university in the State of Mato Grosso, Brazil. This research, which started in 2015, will have four years of follow-up and is scheduled to end in 2018. A self-administered questionnaire is applied, containing questions regarding demographic and socioeconomic characteristics, and information on health conditions and risk factors such as lifestyle, perceived stress, symptoms of depression, body image, risk behaviors for eating disorders, self-assessment of health and diet quality, and other issues related to nutrition and health. Anthropometric and blood pressure measurements are also recorded. Two 24-hour dietary recalls and cholesterol, triglycerides, and glucose capillary measurements are collected in 50% of the students. In 2015, 495 participants (82.6% of the eligible students) were assessed in the baseline study. Of these, 348 (70.3%) were followed up in 2016. In 2016, 566 participants were included in the cohort (81% of the eligible students). This study will help to identify the factors that might influence changes in the nutritional, health, and metabolic status of young adults during college life.